MOTIVATION OF FUTURE HEALTH CARE SPECIALISTS IN PROMOTING SOCIAL WELLBEING OF ELDERLY PEOPLE - Berloviene, Dina; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Dynamics of ageing of Latvia’s population is faster than in other European Union countries, which has been caused by the social economic situation and immigration of society members. Ageing of society will have a considerable impact on health care in the future. Hence, it is essential to invest resources in the process of the development of health care by educating health care specialists who will be motivated to solve social wellbeing problems in the country in a professional way.Students and lecturers of Riga Stradins University Liepaja branch have been taking part in European Later Life Active Network (ELLAN) project since 2013. In the research done within the framework of the project, Kogan’s attitude scale to elderly people has been made use of, as well as Nolan’s questionnaire was used to learn about the future health care specialists’ attitude and their expectations concerning work with elderly people. Data collected in Latvia in comparison with the rest of the four countries (Ireland, Germany, Italy and Finland) taking part in the project present the lowest level of attitude indicators. The article focuses on the issue of future health care specialists’ motivation and attitude in their professional work with elderly people, as well as, the impact of the environment on promoting the development of positive attitude towards elderly people and work with them during the study process.